UNDERSTANDING EFFECTS OF CHOLESTEROL LOWERING THERAPIES ON THE PROGRESSION OF DIABETIC NEPHROPATHY RENOPROTECTION - AUGUSTIN KUMAR BHARTI (International Journal of Pharma and Bio Sciences, 2014)
Diabetic Nephropathy (DN) is a leading cause of morbidity and mortality and its prevalence is continuously increasing in industrialized nations. Hyperglycemias, hyperlipidaemia and hypertension are underline factors that are addressed in the progression of diabetic nephropathy. Glomerular injury is linked to an increase in lipoprotein synthesis and a decrease in peripheral lipoprotein catabolism. These abnormalities often lead to marked increases in total plasma cholesterol concentrations, particularly very low-density lipoprotein and low-density lipoprotein (LDL) fractions. The extracellular mesangial matrix is capable of binding considerable amounts of LDL or modified LDL. Cross linking of mesangial matrix with LDL, mimicking the progression of glomerular lesion in DN. At present, no promising therapy is available to treat patients with DN due to lack of understanding of mechanism involved in the pathogenesis of nephropathy. Through this review we are trying to explore the, use of cholesterol lowering therapies, which will provide potential therapeutic benefit to diabetic nephropathy.